Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I prove that :

$$b_{A}=\frac{1}{b+c} \cdot \sqrt{bc\left[(b+c)^2-a^2\right]} ?$$ where $b_{A}$ is the length of the bisector from $A$ .

Thanks :)

share|cite|improve this question
what are $a,b,c?$ Is this a triangle and $a,b,c$ the sides with $A$ the angle opposite $a$? – Ross Millikan Nov 12 '12 at 15:58
yes, it is the normally notation :) – Iuli Nov 12 '12 at 16:00
It is, but much easier to remember when you are in the middle of a geometry class. We see many subjects here, so it would be helpful to include that in the question. – Ross Millikan Nov 12 '12 at 16:05
Have you tried writing the law of cosines for each of the two small triangles, then eliminating $\cos \frac A2$ between the two equations? It looks like it should work. – Ross Millikan Nov 12 '12 at 16:09
up vote 1 down vote accepted

Let $P$ be the point where the bisector of $\angle A$ meets $BC$. Let $x=BP$ and $y=PC$. Then $x+y=a$. Moreover, by a standard theorem on angle bisectors, we have $\dfrac{x}{c}=\dfrac{y}{b}$, or equivalently $bx=cy$.

We have two linear equations in two unknowns. Solve for $x$ and $y$. We obtain $$x=\frac{ac}{b+c}\qquad\text{and}\qquad y=\frac{ab}{b+c}.$$

Now let $\theta=\angle APB$ and $\phi=\angle APC$. Then $\cos\phi=-\cos\theta$. By the Cosine Law on $\triangle BPA$, we have $$c^2=b_A^2+x^2 -2b_A \,x\cos\theta.\tag{$1$}$$ Similarly $$b^2=b_A^2 +y^2+2b_A \,y\cos\theta.\tag{$2$}$$ Multiply both sides of $(1)$ by $y$, and both sides of $(2)$ by $x$, and add. We get $$yc^2+xb^2=(x+y)b_A^2+xy(x+y).$$ Substituting our values for $x$ and $y$, and noting that $x+y=a$, we obtain $$\frac{abc^2}{b+c}+\frac{acb^2}{b+c}=ab_A^2+\frac{a^3bc}{(b+c)^2}.$$ This simplifies to $$bc=b_A^2+\frac{a^2bc}{(b+c)^2},$$ or equivalently $$b_A^2=\frac{1}{(b+c)^2}\left(bc\left[(b+c)^2-a^2\right]\right),$$ which is what we wanted to show.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.